Data Integration for Sustainable Governance in Sport Education and Counselling in Nigeria - Adaobi Jennifer Iloakasia; Yumna Syaza Kani Putri (Siber International Journal of Sport Education, 2025)
In Nigeria, sport education and counselling play a vital role in nurturing physical, emotional, and social development, yet their governance often faces challenges linked to fragmented data systems and weak coordination. Without integrated data, planning, evaluation, and accountability in sport and counselling programs remain inconsistent. This study therefore explored how data integration contributes to sustainable governance in sport education and counselling, emphasizing its role in improving transparency, resource utilization, and evidence-based decision making. Data were collected from 178 participants through a validated questionnaire and analyzed with the Statistical Package for the Social Sciences. Descriptive and inferential statistics, including Spearman’s correlation and multiple regression, were applied to test the relationship between the variables. The results showed that both data integration (p = .001) and sustainable education governance (p = .000) were not normally distributed, justifying the use of Spearman’s correlation. The correlation analysis revealed a strong positive relationship (r = .594, p = .000) between data integration and sustainable education governance, meaning that improved data systems enhance decision making and sustainability in governance. The study concludes that building reliable data systems and promoting digital literacy among sport and counselling professionals are essential for achieving sustainable governance outcomes in Nigeria.